2016
DOI: 10.1080/23337931.2016.1239182
|View full text |Cite
|
Sign up to set email alerts
|

Influence of niobium pentoxide addition on the properties of glass ionomer cements

Abstract: Objective: To determine the influence of niobium pentoxide (Nb2O5) addition on the physical and chemical properties of glass ionomer cements (GICs). Materials and methods: Five, 10 or 20 wt.% of Nb2O5 were incorporated into commercial GICs (Maxxion R, Vitro Molar, Vitro Fil R) and one group of each GIC remained without Nb2O5 (control groups). The GICs were evaluated by Knoop hardness, compressive strength, acid erosion, particle size and radiopacity. Data were analyzed by two-way ANOVA followed by Tukey's test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The authors concluded that these results are positive and further investigations are required to analyze the biomimetic remineralization potential of this material. 47…”
Section: Glass Ionomer Cement Powder Modifications and Filler Incorpomentioning
confidence: 99%
“…The authors concluded that these results are positive and further investigations are required to analyze the biomimetic remineralization potential of this material. 47…”
Section: Glass Ionomer Cement Powder Modifications and Filler Incorpomentioning
confidence: 99%
“…Incorporation of niobium pentaoxide to luting GICs was reported to decrease their compressive strength significantly [ 15 ]. However, in recent years, it has been demonstrated that 5% niobium pentoxide can be added to improve the radiopacity of GIC without affecting its strength [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is an important observation, as the collagen membrane in the procedures was left exposed after the ap repositioning. The exposure of membrane after guided bone regeneration membranes is known to increase the prevalence of postoperative bacterial infection in surgical sites [38]. Furthermore, the cyanoacrylate-based adhesive (Periacryl® 90 HV) exhibited a hemostatic effect on the wound after 12 days, when the sockets already had brin formation, indicating a beginning of wound healing [39].…”
Section: Discussionmentioning
confidence: 99%